Analysis of Character Educational Values in the Main Characters of the Lion King’s Movie - Roihani Faiziyah; Muhammad Zikri; Tirta Rhamadanty; Zulkifli Lessy (Proceeding International Conference on Religion, Science and Education, 2023)
Character is the most basic and very important and fundamental thing that every human being must have. Strengthening character education in the current context is very important to overcome the moral crisis or social phenomenon thatis currently happening in our country. The behaviour of today’s youth is also characterized by cheating, habit of breaking school rules, and conflicts. This research aims to investigate, (1) What types of Character Educational Values are found in the Lion King’s movie?, (2) What is the implication of Character Educational Values in The Lion King’s movie? and (3) What are the correlations between Character Educational Values in The Lion King’s Movie and SocialPsychology I n students’. This study applied descriptive qualitative method to describe characters educational values inside The Lion King movie and presented it as students’ characters building. The results of this study showed that there are two groups to analyze the educational values. There are values of being and values of giving. Then, Simba and Mufasa’s characters enter into 3 social contexts, namely self-concept, self-image and self-efficacy. Therefore, Simba’s characters and behaviour were influenced by his family and social environment.